ANALISIS GEOSTRATEGI AFRIKA SELATAN SEBAGAI REGIONAL POWER DALAM KERANGKA UBUNTU DIPLOMACY TERHADAP REPUBLIK DEMOKRATIK KONGO - Bintang Corvi Diphda; Alia Rahma Putri Sinaga; Putri Alyaa Safira; Gertha Maria Gultom; Yoga Ramadhani; Angelique Kishiola Prima Foraihmbarasi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This article examines South Africa’s geostrategy as a regional power through Ubuntu Diplomacy toward the Democratic Republic of Congo (DRC) from 2011 to 2022. It aims to explain how South Africa’s stable border orientation enabled power projection to a non-neighbouring state and how Ubuntu Diplomacy framed this process. The study uses a case study design. Using Jakub J. Grygiel’s geostrategy framework, the analysis first assesses South Africa’s state borders and border pressure, then maps power projection in the DRC across diplomatic-political, military, and economic instruments. The findings show that relatively stable borders reduced defensive constraints and facilitated long-range power projection, while Ubuntu Diplomacy provided normative justification for these policy choices.